Evidence of Non-microtubule Spindle Forces in Mesostoma ehrenbergii Spermatocytes - Fegaras-Arch, Eleni; Berns, Michael; Forer, Arthur (Frontiers in Molecular Biosciences, 2020)
Mesostoma spermatocyte chromosomes moved rapidly to a pole in the absence of microtubules (Fegaras and Forer, 2018 a and b): after 10µM nocodazole (NOC) depolymerized metaphase spindle microtubules, kinetochores from each of the 3 bivalents detached from the same pole and rapidly moved to the other pole, at speeds averaging 35.1 µm/min. with some speeds as high as 100µm/min. We argued that these very fast movements were due to non-microtubule forces arising from a spindle matrix. However, since the chromosomes stretch out before detaching there is tension in the chromosomes from the stretch, so the movements of detached kinetochores conceivably might be due to recoil from the tension. This did not seem to us to be the case because the moving kinetochores followed curvilinear paths, appearing to arise from external forces rather than linear recoil. In this article we further test this possibility. We cut bivalents into 2 pieces using a femtosecond laser, either before or after addition of NOC. When 1 bivalent was severed, all kinetochores moved to one pole in 13/15 cells; when 2 bivalents were severed, all kinetochores moved to one pole in 4/6 cells; and when all 3 bivalents were severed all kinetochores moved to one pole in 5/9 cells. The bivalent 'halves' moved rapidly to the opposite pole with average speeds of 47 µm/min when including cells with 1, 2, or 3 bivalents cut quickly; these velocities were not significantly different from those in cells without any laser-cut bivalents (p<0.05). Since kinetochores move at the same speeds whether they are part of bivalents or are 'halved' bivalents, NOC-induced chromosome movements are not due to recoil, strongly supporting the idea that non-microtubule forces move chromosomes in Mesostoma spermatocytes.